1994
DOI: 10.1007/bf02362026
|View full text |Cite
|
Sign up to set email alerts
|

The potentials of magnetic resonance tomography in the diagnosis of the “empty” sella turcica

Abstract: The term ~empty" sella turcica (EST) was first introduced by Bush in 1951, when in describing the data of 788 autopsies, the diaphragm of the sella was completely lacking in 5.5% of cases, and the hypophysis was spread out on the floor in the form of a thin lamina. This being the case, the sella appeared empty. As a disease, the EST was described in 1962 in patients subjected to surgical or radiation therapy because of endosellar adenoma of the hypophysis. It was later related to the syndrome of secondary EST.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In total, 165 subjects were included from the 29 studies. Of these, 46 subjects were in studies on primary hypothyroidism [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] (i.e. in which hypothyroidism was related to ID), 97 subjects in studies on congenital hypothyroidism [67][68][69][70][71][72][73][74][75][76][77], 3 subjects in a study of endemic cretinism [78], 11 subjects in a study of subclinical hypothyroidism [79,80] and 8 subjects in a study of perinatal hypothyroidism [80] (Figure 2).…”
Section: Sample Sizementioning
confidence: 99%
See 2 more Smart Citations
“…In total, 165 subjects were included from the 29 studies. Of these, 46 subjects were in studies on primary hypothyroidism [52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] (i.e. in which hypothyroidism was related to ID), 97 subjects in studies on congenital hypothyroidism [67][68][69][70][71][72][73][74][75][76][77], 3 subjects in a study of endemic cretinism [78], 11 subjects in a study of subclinical hypothyroidism [79,80] and 8 subjects in a study of perinatal hypothyroidism [80] (Figure 2).…”
Section: Sample Sizementioning
confidence: 99%
“…T2-weighted (T2W) sequence was utilised in 11/29 studies whilst 6/29 studies did not clarify the MRI sequence used. In 2 studies, only 60% of the hypothyroid patients showed brain changes on MRI [54,74] (Table 3).…”
Section: Type Of Mr Confirmationmentioning
confidence: 99%
See 1 more Smart Citation